Assessing Fungal Diversity and Abundance in the Black Soldier Fly and its Environment. Issue 6 (18th November 2022) - Vitenberg, Tzach; Opatovsky, Itai
Abstract: Detritivorous insects that flourish in decaying environments encounter microorganisms throughout their life cycle. However, it is not clear whether the microbial composition of the decaying environment affects the microbial composition of the insect gut, or whether the opposite is true, with the microorganisms that are adapted to the insect's digestive system being dispersed by the insects to new habitats, thereby becoming more and more common in the environment. To test these questions the fungal composition of the black soldier fly (BSF) (Stratiomyidae; Hermetia illucens Linnaeus) larval gut and its surrounding decaying environment (household compost bins) were analyzed using amplicon sequencing. Constancy in the dominance of the genus Candida (Debaryomycetaceae) in most of the environments and larval guts was found. This finding may suggest a 'core' structure to the fungal community of the BSF. In locations where nutrient composition of the environment had higher fiber content, the Candida was not dominant and the most common fungi were the genus Gibberella (Nectriaceae) and the family Dipodascaceae. The later was dominant also in the larval gut and the former was replaced with Meyerozyma (Debaryomycetaceae), which may suggest a selection process by the insect's gut. Little is known about the ecological interactions of insects with eukaryotic microorganisms, such as yeast-like fungi. As their metabolic complexity and ability is intense, they have the potential to dramatically affect the physiological condition of the insect.